2011
DOI: 10.1002/ijc.25757
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin (IL)‐18, a biomarker of human ovarian carcinoma, is predominantly released as biologically inactive precursor

Abstract: Interleukin (IL)-18 is a proinflammatory and immune-enhancing cytokine, which exerts antitumor effects in vivo, mediated by the induction of interferon (IFN)c. We previously reported that IL-18 processing is defective in epithelial ovarian carcinoma (EOC) cells, which secrete an inactive precursor (pro-IL-18) in vitro. In addition, IL-18 was reported as a potential biomarker of EOC. Here, we further investigated its role as a serological marker in human EOC and addressed its possible biological activity in viv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 47 publications
3
19
0
Order By: Relevance
“…Jaime-Ramirez et al [33] have shown that IL-12 enhances the antitumour actions of trastuzumab via NK cell IFN-γ production, and deficiencies in antigen presentation and IL-1 production by cancer patients' monocytes have been previously published by our group [34], as well as others [35,36]. Such abnormalities in antigen-presenting cell functions, and in particular those of reduced IL-12 and IL-18 production, further support the notion of a shift towards a Th2 type of response in cancer patients [37,38,39,40]. …”
Section: Discussionsupporting
confidence: 60%
“…Jaime-Ramirez et al [33] have shown that IL-12 enhances the antitumour actions of trastuzumab via NK cell IFN-γ production, and deficiencies in antigen presentation and IL-1 production by cancer patients' monocytes have been previously published by our group [34], as well as others [35,36]. Such abnormalities in antigen-presenting cell functions, and in particular those of reduced IL-12 and IL-18 production, further support the notion of a shift towards a Th2 type of response in cancer patients [37,38,39,40]. …”
Section: Discussionsupporting
confidence: 60%
“…It was previously shown that high levels of IL-18 are present in serum and ascites of patients with EOC (12) and that pro-IL-18 is largely predominant (13). In fact, although IL-18 ELISA preferentially recognized mat-IL-18 in sera, this assay also detected pro-IL-18, albeit with a reduced sensitivity.…”
Section: Discussionmentioning
confidence: 92%
“…Some of these cytokines have been considered as serologic biomarkers of EOC (11). Among them, interleukin (IL)-18 was proposed as a potential biomarker by gene expression profiling (12) and, indeed, IL-18 levels were elevated in serum and ascites of patients with EOC (12,13).…”
Section: Introductionmentioning
confidence: 99%
“…Higher IL18 levels in patient plasma correlated with a longer survival time, but higher IL18 levels in cancer tissues correlated with shorter survival time. In ovarian cancer, tumor cells predominantly release the biologically inactive 24-kDa pro-IL18 (23), and only this form is detectable in the ascites of patients (24). We therefore chose an antibody specific to mature form IL18 in pancreatic cancer patients' plasma and tissues directly.…”
Section: Discussionmentioning
confidence: 99%